A NEW LIFETIME DISTRIBUTION - Celik, Nuri; Guloksuz, Cigdem Topcu (Polish Maintenance Soc, 2017)
The well-known statistical distributions such as Exponential, Weibull and Gamma distributions have been commonly used for analysing the different types of lifetime data. In this paper, following the idea of the extension of T-X family of distributions, we propose a new type of exponential distribution. We define the survival function, the hazard function and the mean time to failure related to this new distribution. Type II censoring procedure is also considered for this distribution. Additionally, stress-strength reliability and the maximum likelihood (ML) estimators of the unknown parameters are obtained. As an application, a real data set is used to show that the proposed distribution gives best fit than the alternative ones.
Keywords: T-X Family Of Distributions; Reliability Function; Hazard Rate; Type Ii Censoring; Stress-Strength Probability